2021
DOI: 10.3390/jcm10081622
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Temporary Stay at High Altitude on the Circulatory System

Abstract: In recent times many people stay temporarily at high altitudes. It is mainly associated with the growing popularity of regular air travel, as well as temporary trips to mountain regions. Variable environmental conditions, including pressure and temperature changes, have an impact on the human body. This paper analyses the physiological changes that may occur while staying at high altitude in healthy people and in people with cardiovascular diseases, such as arterial hypertension, pulmonary hypertension, heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 68 publications
2
12
0
1
Order By: Relevance
“…Concordant with previous studies ( 30 , 31 ), we found that HH-induced tachycardia and prolongations of QT, QTc, JT, and Tpeak-Tend intervals, and ST height, P duration, and R and T amplitudes. Reportedly, these observations are because at HH; there is an increase in sympathetic activity, which triggers prolongation of repolarization, resulting in arrhythmia, heart failure, and sudden death ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…Concordant with previous studies ( 30 , 31 ), we found that HH-induced tachycardia and prolongations of QT, QTc, JT, and Tpeak-Tend intervals, and ST height, P duration, and R and T amplitudes. Reportedly, these observations are because at HH; there is an increase in sympathetic activity, which triggers prolongation of repolarization, resulting in arrhythmia, heart failure, and sudden death ( 30 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to cardiac overload, the incidences of hyperhemoglobinemia, hyperlipemia, and hypercoagulability are also higher than those found in patients living in plain areas (8). Furthermore, reduced oxygen supply and hyperlipidemia contribute to coronary heart disease and other cardiac events (9). Living at high altitude also increases the risks of deep vein thrombosis and pulmonary embolism after surgery, which is believed to be related to the pathological state of highaltitude polycythemia, venous stasis and hypercoagulability (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…High-altitude (HA) locations (more than 2500 m above sea level) are reached by millions of people on a daily basis, aspect largely due to the ease of transport in recent years, mainly by air travel. Mountain areas cover 24% of Earth’s surface: 33% of Eurasia, 19% of South America, 24% of North America, and 14% of Africa [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The barometric pressure drops gradually with increasing altitude and the temperature also decreased. The human body must and has the ability to adapt to climatic and environmental conditions and the circulatory system plays a major role in this process [ 1 ].…”
Section: Introductionmentioning
confidence: 99%